2016
DOI: 10.1016/j.tiv.2016.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapeutic efficiency of drugs in vitro: Comparison of doxorubicin exposure in 3D and 2D culture matrices

Abstract: The interest in the use of 3D matrices for in vitro analysis, with a view to increasing the relevance of in vitro studies and reducing the dependence on in vivo studies, has been growing in recent years.Cells grown in a 3D in vitro matrix environment have been reported to exhibit significantly different properties to those in a conventional 2D culture environment. However, comparison of 2D and 3D cell culture models have recently been noted to result in differing responses of cytotoxic assays, without any asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…Protein coated substrates [148] and 3-D matrices have also been explored to improve measurement protocols [149,150]. Bonnier et al [151], and Casey et al [152] have demonstrated that caution must be taken when applying conventional 2D cytotoxicity assay and drug dosing protocols to cells in a 3D environment, due to differing bioavailabilities of the assay or drug. Nevertheless, it is generally accepted that such 3D environments better mimic the in vivo extracellular matrix.…”
Section: Ex-vivo -Liquid Biopsiesmentioning
confidence: 99%
“…Protein coated substrates [148] and 3-D matrices have also been explored to improve measurement protocols [149,150]. Bonnier et al [151], and Casey et al [152] have demonstrated that caution must be taken when applying conventional 2D cytotoxicity assay and drug dosing protocols to cells in a 3D environment, due to differing bioavailabilities of the assay or drug. Nevertheless, it is generally accepted that such 3D environments better mimic the in vivo extracellular matrix.…”
Section: Ex-vivo -Liquid Biopsiesmentioning
confidence: 99%
“…doxorubicin-induced CMC-toxicity requires further investigation, by also assessing apoptotic cell death, as an important parameter in doxorubicin toxicity, for all cell types. Furthermore, possible variation in exposure conditions and uptake kinetics of drugs and reagents between 2D and 3D culture cannot be excluded as a contributing factor to the observed reduced doxorubicin-induced toxicity in our 3D environment (Casey et al, 2016). The concentration ranges of doxorubicin used in the present study are within the ranges that the cells are exposed to in vivo (Gunven et al, 1986;Barpe et al, 2010).…”
Section: Cardiomyocytes In a Tri-culture Model Systemmentioning
confidence: 77%
“…Within our tri‐culture system, the specific role of the SMCs in influencing doxorubicin‐induced CMC‐toxicity requires further investigation, by also assessing apoptotic cell death, as an important parameter in doxorubicin toxicity, for all cell types. Furthermore, possible variation in exposure conditions and uptake kinetics of drugs and reagents between 2D and 3D culture cannot be excluded as a contributing factor to the observed reduced doxorubicin‐induced toxicity in our 3D environment (Casey et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Spheroid models have been used primarily as an in vitro model for three-dimensional solid tumors to investigate mechanisms of drug resistance 42 . Spheroid cells are known to become refractory to conventional chemotherapeutic agents, especially to paclitaxel when compared to monolayer cells 43, 44 . Therefore, eradication of spheroids within ascites may be quite clinically relevant to decrease the high rate of ovarian cancer recurrence.…”
Section: Discussionmentioning
confidence: 99%